Applying theory of planned behavior on entrepreneurial intent among Malay accounting students in Malalysia - Bidin, Zainol; Mohd Shamsudin, Faridahwati; Othman, Zainudin (2012)
The Malaysian government is strongly promoting entrepreneurship as a career choice among students. However, many students do not turn out to be entrepreneurs after their graduation, especially Malays, despite the government call. It is proposed in this paper that students’ behavior and decision to become entrepreneurs can be explained by their intention, which is influenced by three factors i.e. attitude towards entrepreneurship, subjective norms, and perceived behavioral control. Therefore, theory of planned behavior (TPB), developed by Ajzen (1985), was applied as a basis for this study. A sample of 141 final year Malay accounting students selected randomly in two public universities in Malaysia were asked to complete questionnaires with 18 items that measured all variables under study. Descriptive and inferential analyses were run to test the hypotheses formulated. Multiple regression analyses were specifically conducted to test the model derived from TPB. Findings show that the model is valid in predicting entrepreneurial intention. In particular, the study shows that all three factors significantly influence students’ intention to be an entrepreneur. Perceived behavioral control emerged as the strongest factor that influences intention. The study’s findings have important implications especially to policy makers in promoting and developing future entrepreneurs in Malaysia such as in the area of entrepreneurship education.